2021
DOI: 10.1021/acscatal.1c00940
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodechlorination of 1,2-Dichloroethane on Platinum Catalysts: Insights from Reaction Kinetics Experiments, Density Functional Theory, and Microkinetic Modeling

Abstract: Catalytic hydrodechlorination is a promising strategy for treating industrial 1,2-dichloroethane wastes, for which Pt and Pt-based alloy catalysts are widely used. Here, we performed a detailed mechanistic study for 1,2-dichloroethane hydrodechlorination on Pt using a synergistic approach combining density functional theory (DFT) calculations, reaction kinetics experiments, and microkinetic modeling. Using planewave DFT calculations, we evaluated the reaction energy and activation energy barrier of each elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…Previously, we examined the 1,2-DCA hydrodechlorination mechanism on pure Pt catalysts using a combination of reaction kinetics experiments, density functional theory (DFT) calculations, and mean-field microkinetic modeling. 37 We demonstrated that 1,2-DCA hydrodechlorination on pure Pt catalysts starts with a hydrogen-removal step and proceeds through the following reaction pathway (eq 1):…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, we examined the 1,2-DCA hydrodechlorination mechanism on pure Pt catalysts using a combination of reaction kinetics experiments, density functional theory (DFT) calculations, and mean-field microkinetic modeling. 37 We demonstrated that 1,2-DCA hydrodechlorination on pure Pt catalysts starts with a hydrogen-removal step and proceeds through the following reaction pathway (eq 1):…”
Section: ■ Introductionmentioning
confidence: 95%
“…We previously demonstrated the success of this combined experimental and theoretical approach for the study of the same chemistry on pure Pt catalysts. 37 Using DFT calculations, we first studied the effect of Pt−Cu alloy composition on the binding properties of surface reaction intermediates. The reaction kinetics of surface elementary steps were then examined on Pt 1 Cu 3 (111), a Curich alloy model surface for the Pt−Cu catalysts used in our reaction kinetics experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2-Dichloroethane (DCE) has found widespread applications as universal synthetic intermediates in organic chemistry owing to the inherent reactivity of carbon–chlorine bonds. , However, the excessive emissions of DCE with higher toxicity and lower biodegradability have made it classified as a priority pollutant in most countries. , Therefore, it is of great significance to develop efficient and applicable remediation strategies for the elimination of DCE. In our previous studies, we confirmed that dislodging DCE through electrochemical dechlorination is an economic and eco-friendly method to selectively produce ethylene, which is one of the most important feedstocks in petrochemical industries. However, due to the stability of the C–Cl bond (327 kJ·mol –1 ) and the poor selectivity and Faradaic efficiency, the development and application of DCE dechlorination reaction have been limited .…”
Section: Introductionmentioning
confidence: 99%
“…■ INTRODUCTION 1,2-Dichloroethane (DCE) has found widespread applications as universal synthetic intermediates in organic chemistry owing to the inherent reactivity of carbon−chlorine bonds. 1,2 However, the excessive emissions of DCE with higher toxicity and lower biodegradability have made it classified as a priority pollutant in most countries. 3,4 Therefore, it is of great significance to develop efficient and applicable remediation strategies for the elimination of DCE.…”
mentioning
confidence: 99%
“…The common catalysts used for HDC are supported noble metals, for example, Pd, , Ru, and Rh, , while transition metals, such as Ni and Co, are effective for this reaction but require relatively critical reaction conditions. To achieve better performance, bimetallic alloy catalysts, for instance, PdAg, PtNi, NiFe, and PdNi, have also been studied, and their performances are usually dependent on the compositions of bimetallic alloys. , Among various catalysts, Pd has been recognized as efficient catalysts for HDC of various chlorophenols, which can be performed at atmospheric H 2 pressure and low temperatures.…”
Section: Introductionmentioning
confidence: 99%